(untitled) (Journal of Humanitarian and Applied Sciences, 2020)
Popular markets are not a past-remained phenomenon. Their existence is based on the affordability of some economic necessities which require such this cyclic pattern of shopping. This is probably the cause of its activity despite of the social and economic changes that Libya in general and Tarhuna in particular have witnessed. The aim of the research was to shed lights on the necessity of the emergence and development of this pattern of markets in addition to the changes intervened to it. Moreover, the research brought into focus the extent of the pattern’s ability for continuity and its impact on the functionality of markets especially that these markets have been affected by civilized progress and high living standards, let alone that their cyclic system permits a kind of economic integration although of their random distribution. The study recommended the necessity of activating the governmental role in order to increase the concern about other popular markets as a historical and heritage phenomenon by planning and preparing them with services similar to the experience of Alkhadra popular market in Tarhuna.